2022
DOI: 10.3390/ijerph19116601
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Current Endodontic Practices among General Dental Practitioners in the Kingdom of Saudi Arabia

Abstract: A contemporary knowledge of root canal treatment (RCT) is a prerequisite for a successful outcome. Studies observed that General Dental Practitioners (GDPs) were not abreast of current endodontic knowledge due to a lack of continuing dental education, not following the treatment protocols that they had learned in their undergraduate program, and overlooking the evidence-based current endodontic practices. Therefore, this study was intended to assess the awareness, attitude, and clinical endodontic practices am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 43 publications
0
5
1
Order By: Relevance
“…They aim to activate irrigants chemically and mechanically thereby improving their antimicrobial and tissue-dissolving e ciency and enhancing the irrigant's penetration into the complex root canal anatomy including lateral ns by displacing the apical 'vapour lock' effect [3,14,28]. 40.1% of the respondents from our study used manual dynamic agitation which is encouraging as it is a simple and cost-effective method proven to be more effective than static needle-and-syringe irrigation [29]. In the absence of more advanced adjunct techniques, it is strongly recommended that clinicians incorporate this technique into their nal irrigation protocol.…”
Section: Discussionmentioning
confidence: 71%
“…They aim to activate irrigants chemically and mechanically thereby improving their antimicrobial and tissue-dissolving e ciency and enhancing the irrigant's penetration into the complex root canal anatomy including lateral ns by displacing the apical 'vapour lock' effect [3,14,28]. 40.1% of the respondents from our study used manual dynamic agitation which is encouraging as it is a simple and cost-effective method proven to be more effective than static needle-and-syringe irrigation [29]. In the absence of more advanced adjunct techniques, it is strongly recommended that clinicians incorporate this technique into their nal irrigation protocol.…”
Section: Discussionmentioning
confidence: 71%
“…Additionally, a study conducted by Nezar in 2021 showed a reasonably good usage rate (71%) of rubber dams among the study participants [ 13 ]. Jouhar et al found most participants used rubber dams (74.0%) [ 2 ]. This contrasted our study findings, which showed a very low usage (22.66%) of rubber dams by dental practitioners.…”
Section: Discussionmentioning
confidence: 99%
“…The primary objective in endodontics is the elimination of microorganisms infecting the root canal system. This requires rigorous aseptic protocols and isolation of saliva, blood, and other gingival fluids [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of the small differences, we observed that the CWC technique provided the lowest microleakage values whereas the highest microleakage levels were recorded with the SC technique using BC-coated GP. Previous studies have reported that warm compaction techniques adversely affect the sealing ability of calcium silicate sealers as heat negatively affects flow, setting time and residual moisture content in canals and dentinal tubules [ 7 , 33 , 34 , 35 ]. Contrary to these findings, other authors have reported favorable results when using the CWC technique and calcium silicate sealers.…”
Section: Discussionmentioning
confidence: 99%